Relationship between Norm of Social Reciprocity and Law-breaking among Motorcycle Users in Yazd - Ebrahim Masoudnia (جامعه شناسی کاربردی, 2014)
Introduction Crime, irregularity and fear of insecurity, are the most important determinants of a community's failure to achieve collective goals in the path to individual and social well-being. Hence, to ensure security and prevent anti-social behavior, human societies created a set of rules and norms for monitoring and controlling anti-social behavior. But in all societies, especially developing ones, there are people who ignore these rules. Inattention to these rules can lead to road accidents, high mortality, physical damage, disruption of family after accident, and costly financial damage. According to estimates, in 2020, road traffic accidents will become the third leading cause of death worldwide. In Iran, traffic accidents, has been on an increasing path to the extent that its growth is 10% and the rate of deaths from traffic accidents, is 15 times higher than that of the developed countries. Previous research on the etiology of law breaking among motorcycle users often focused on physical and psychological risk factors. This study aims at explaining the relationship between the norm of reciprocity (as a component of social capital) and violation of traffic rules by motorcycle users based on social capital theory.